Pravidla buněčného škálování mozku u psů: Efekt domestikace a miniaturizace psích plemen - Salajková, Veronika (Univerzita Karlova, Přírodovědecká fakulta, 2020)
The process of domestication of the grey wolf (Canis lupus) resulted in more than 350 dog breeds attesting for an immense phenotypic plasticity of this species, reflected in the enormous variation of sizes, shapes and behavioural profiles of today's dogs. The differences in body size can be 50-fold, which exceeds the body size variation of all recent canids. The differences in brain size are significantly smaller, only about 2.5-fold. It is also well known that, compared to their wolf ancestor, dogs, and especially small breeds, have reduced brain size. However, up till now, no comparative data about neuron numbers in different dog breeds are available. In this thesis, I use the isotropic fractionator to assess number of neurons and glial cells in eight dog breeds and three species of wild canids. When compared across dog breeds analysed, the differences in neuron numbers are lower than the differences in brain size - it seems that small breeds compensate for smaller brains with higher neuronal density. Interestingly, miniaturization of dog breeds is associated with brain size reduction that is smaller than expected from brain-body scaling reported for wild canids and seems to be accompanied by compensatory increase of neuronal density. Thus, brains of small dogs are bigger and harbour more neurons. Proces domestikace vlka obecného (Canis lupus) vyústil do současných více než 350 psích plemen, dokládající enormní fenotypickou plasticitu tohoto druhu odraženou v nesmírné rozmanitosti velikostí, tvarů a behaviorálních profilů dnešních psů. Až 50násobné rozdíly ve velikosti těla přesahují variabilitu ve velikosti těla v rámci celé skupiny Canidae. Rozdíly ve velikosti mozku jsou však o poznání menší, a to přibližně 2,5násobné. Je také dobře známo, že ve srovnání s vlčím předkem mají psi, především malá plemena, zredukovanou velikost mozku. Avšak, dosud nejsou k dispozici srovnávací kvantitativní data o počtech neuronů pro různá psí plemena. V předložené diplomové práci jsem pomocí metody izotropní frakční ...